Challenges in Developing Ecotourism in The Region of Lake Sentani Papua - Sitorus, Yannice Luma Marnala; Rosyidie, Arief; Suhirman, Suhirman (E-Journal of Tourism, 2017)
The concept of community-based ecotourism is one of the sustainable development concepts suitable to be applied to traditional regions with nature tourism potential. Differences in culture between traditional communities and the outside world are not an obstacle in developing the region because with their local wisdom traditional communities can participate in protecting and managing their natural surrounding and at the same time become an attraction for other communities. However, outside societies can influence the culture of the traditional communities that originally tends to be oriented on biocentrism to shift towards anthropocentrism. This can eventually hamper the continuity of ecotourism development. This can be seen from the traditional communities at Lake Sentani, the case study of the author. The study is based on literature and secondary data and used descriptive analysis. The traditional communities of Sentani do not yet fully participate in the development of tourism in its surroundings. Their involvement in tourism development is more focused on ceremonial activities such as can be seen at the Lake Sentani Festival which is organized every year by the government. Besides this, after coming into contact with modern life the traditional communities of Lake Sentani rarely perform their daily activities based on local wisdom aimed at natural conservation of the lake. The development of urban areas in the surroundings also influences changes in land use in the Lake Sentani region which then causes among others erosion, sedimentation, and pollution of the lake water. Socio-economic and cultural changes in the traditional communities of Sentani and the growth of development also contribute towards ecological change in the area of Lake Sentani, the place they live in.
Keywords: ecotourism; traditional communities; cultural change